The Leaf Morphology of Plant Species at LKPB, Department of Biology, UNM - Muliana GH (PT. Ininnawa Paramacitra Edukasi, 2024)
This study is an initial research effort aimed at reporting, describing, and documenting the leaf morphology of plants found in the LKPB (Laboratory of Biological Experiment Garden) at the Department of Biology, UNM. Plant samples were collected from the LKPB yard using a plot method. The leaf morphology of 51 species has been described and documented. The leaf shapes observed vary, including cordate, ovate, obovate, triangular, oblong, lanceolate, deltoid, and cuneate forms. Some plant species have simple leaves, while others belong to the category of compound leaves. The findings of this study will be further developed into educational materials, booklets, or field practice guides for courses on plant morphology and higher plant botany. Keywords: Plant morphology, leaves, leaf shape, field practice guide